2004
DOI: 10.1073/pnas.0304860101
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells cross-present HIV antigens from live as well as apoptotic infected CD4 + T lymphocytes

Abstract: A better understanding of the antigen presentation pathways that lead to CD8 ؉ T cell recognition of HIV epitopes in vivo is needed to achieve better immune control of HIV replication. Here, we show that cross-presentation of very small amounts of HIV proteins from apoptotic infected CD4 ؉ T lymphocytes by dendritic cells to CD8 ؉ T cells is much more efficient than other known HIV presentation pathways, i.e., direct presentation of infectious virus or crosspresentation of defective virus. Unexpectedly, dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 52 publications
3
68
0
1
Order By: Relevance
“…Consistent with the results reported by Maranon et al [33], we also observed cross-presentation of HIV-1 Ag by iDC following contact with HIV-1-infected cells. Again, our data suggest that both conventional HIV-1 Ag presentation and cross-presentation correlate with high levels of Env-dependent virion endocytosis.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with the results reported by Maranon et al [33], we also observed cross-presentation of HIV-1 Ag by iDC following contact with HIV-1-infected cells. Again, our data suggest that both conventional HIV-1 Ag presentation and cross-presentation correlate with high levels of Env-dependent virion endocytosis.…”
Section: Discussionsupporting
confidence: 82%
“…Other viral antigens have also been shown to be cross-presented in vitro including vaccinia virus, canarypox virus, HIV and HCMV, amongst others [78][79][80][81][82][83]. This crosspresentation suggests a mechanism for the antigen transfer between DC subtypes observed in murine models and suggests that the immunoevasive mechanisms of costimulatory molecule downregulation and apoptosis of DC by HSV can be counteracted by uptake by bystander DC.…”
Section: Subsets In Innate and Adaptive Immunity To Hsvmentioning
confidence: 95%
“…Thus, internalization of virus via endocytosis appeared to be the prime route for MHC-II- restricted presentation of whole virus-derived antigens by immature and mature DCs (24,40,49). DCs are also especially effective at cross-presenting exogenous viral antigens via MHC-I (28,35,71), and this is partially (ϳ40 to 50%) dependent on the endocytic internalization of infectious or AT-2 HIV, suggesting that fusion may occur in the endosomal compartments of DCs through which viral proteins gain access to the cytosol (39,49). The availability of these routes of antigen processing/presentation likely explain how T-1249 did not impede the activation of SIV-specific T cells.…”
Section: Discussionmentioning
confidence: 99%